Comparação entre neurectomia por técnica de guilhotina e neurotomia associada à neurorrafia em alça de balde em nervo digital palmar de éguas - Santana, Taís Brito (2016)
Five mares were submitted to palmar digital neurectomy by the guillotine technique and palmar digital neurotomy followed by end-to-side neurorrhaphy (right and left thoracic limbs, respectively). Mares were checked for local pain sensation using hoof tester and submitted to lameness workup at 15-day intervals. No evidence of painful neuroma formation was detected. Palmar digital nerve (PDN) stump segments were collected within 60 days of surgery. Mean left and right limb PDN stump thickness corresponded to 5.96 mm and 7.16 mm, respectively. Schwann cells prevailed over connective healing tissue in all PDN stumps studied. Well-formed nerve-like structures with better organized nervous tissue and predominance of parallel nerve fiber orientation were documented in left limb PDN stumps. End-to-side neurorrhaphy tended to promote tissue organization, potentially reducing the chances of neuroma formation.